The influence of nutrition and physical activity on exercise performance after mild COVID-19 infection in endurance athletes - CESAR study - Sliz, D.; Wicha, S.; Gasior, J. S.; Kasiak P. S.; Ulaszewska K.; Postula, M.; Malek, L. A.; Mamcarz, A. (Nutrients, 2022)
COVID-19 and imposed restrictions are linked with numerous health consequences, especially among endurance athletes (EA). Unfavorable changes in physical activity and nutrition may affect later sports and competition performance. The aims of this study were: (1) to assess the impact of COVID-19 infection and pandemic restrictions on the nutrition and physical activity of EAs and (2) to compare them with the results of cardiopulmonary exercise testing (CPET). In total, 49 EAs (nmale = 43, nfemale = 6, mean age = 39.9 ± 7.8 year., height = 178.4 ± 6.8 cm, weight = 76.3 ± 10.4 kg; BMI = 24.0 ± 2.6 kg·m-2) underwent pre- and post-COVID-19 CPET and fulfilled the dietary and physical activity survey. COVID-19 infection significantly deteriorated CPET performance. There was a reduction in oxygen uptake and in heart rate post-COVID-19 (both p < 0.001). Consuming processed meat and replacing meat with plant-based protein affected blood lactate concentration (p = 0.035). Fat-free mass was linked with consuming unsaturated fatty acids (p = 0.031). Adding salt to meals influenced maximal speed/power (p = 0.024) and breathing frequency (p = 0.033). Dietary and Fitness Practitioners and Medical Professionals should be aware of possible COVID-19 infection and pandemic consequences among EA. The results of this study are a helpful guideline to properly adjust the treatment, nutrition, and training of EA.